The Red Book of Ukraine of endangered species as an effective mechanism of biodiversity: certain application problems - Єрмолаєва, Тетяна Вікторівна (Problems of legality, 2016)
In the scientific article the author focuses on the major shortcomings of legislation relating to the maintenance of the Red Book of Ukraine and found that it is today effectively prevents the protection and conservation of biodiversity with the specified official document. Paid attention to the problematic aspects of the publication of the third edition of the Red Book of Ukraine; found that pursues the interests of the political elite in the Red Book of Ukraine reprint; expressed criticism of the content of certain requirements of the Law of Ukraine «On the Red Book of Ukraine»; identified gaps within the given legal act. Achieving the goal of scientific research articles contributed chronologically stages of creating Red Book with the assistance of the international community and how international processes influenced the development of the national Red Book of Ukraine.